2001
DOI: 10.1046/j.1365-2362.2001.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐γ in healthy subjects: selective modulation of inflammatory mediators

Abstract: We conclude that IFN-gamma selectively affects host inflammatory mediators in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…In most of the studies exploring IL-8 levels in biological fluids, lower IL-8 concentrations have been detected compared to those used in the present study [42,43]. However, our results are in line with data obtained by Itoh et al [12], who observed a significant IL-8-induced cell proliferation at the same IL-8 concentrations utilized in our study.…”
Section: Discussionsupporting
confidence: 92%
“…In most of the studies exploring IL-8 levels in biological fluids, lower IL-8 concentrations have been detected compared to those used in the present study [42,43]. However, our results are in line with data obtained by Itoh et al [12], who observed a significant IL-8-induced cell proliferation at the same IL-8 concentrations utilized in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Two possible explanations could be provided for these differences in plasma. First, IFN-γ treatment has been shown to decrease levels of PAI-1 in healthy controls [43,44]. Since interferon production in patients with asthma has been shown to be impaired [45-47] this might explain the increased levels of PAI-1 in the present study.…”
Section: Discussionmentioning
confidence: 73%
“…It is rapidly induced and secreted by NK cells after pathogen encounter by the host. Furthermore, macrophage and neutrophil activation by IFN-␥ results in the secretion of tumor necrosis factor alpha (64) and reactive oxygen intermediates (18,19,30). Thus, IFN-␥ is a key mediator of inflammatory responses (8,25).…”
mentioning
confidence: 99%